Fast and Simple Au3+ Colorimetric Detection Using AgNPs and Investigating Its Reaction Mechanism - Faathir Al Faath Rachmawati; Bambang Rusdiarso; Eko Sri Kunarti (Indonesian Journal of Chemistry, 2024)
One of the precious metals that has numerous applications is gold. Although it is non-toxic and biocompatible, the oxidized form, Au3+, is toxic and can cause damage to human organs. Detection of Au3+ becomes a necessary and interesting topic to be conducted. Colorimetric analysis using metal nanoparticles such as silver nanoparticles (AgNPs) can analyze metal ions more simply, sensitively, and selectively than traditional methods. In this research, AgNPs were synthesized using polyvinyl alcohol (PVA) and ascorbic acid as stabilizers and reducing agents. The interaction between Au3+ and AgNPs selectively decreased the absorbance intensity of AgNPs and altered the color of colloidal AgNPs from yellow to colorless. These two phenomena indicated a redox reaction between Au3+ and AgNPs, leading to the decomposition of AgNPs. The decomposition of AgNPs (the proposed mechanism) was confirmed by TEM images and UV-vis spectra. The decrease in AgNPs’ absorbance intensity correlated linearly with the increase in added Au3+ concentration. The calibration curve of ∆A versus Au3+ ion concentration yielded LOD and LOQ of 0.404 and 1.347 μg/mL, respectively.